A critical review of the legal implementation of chemical castration for perpetrators of child sexual abuse - Ziyada Wulan Wulida; Ahmad Mubarak (Priviet Social Sciences Journal, 2026)
Although chemical castration has been recognized in Indonesian child protection law since 2016, its implementation remains normatively and practically problematic, particularly because Government Regulation No. 70 of 2020 requires the sanction to be executed only after the convict has completed the principal sentence. In addition, there is the issue of court rulings that lack enforceability. This study employs a normative legal method using statutory, case, and conceptual approaches to examine Article 9(c) of Government Regulation No. 70 of 2020, selected criminal judgments imposing chemical castration, sentencing principles, medical ethics and human rights standards. The results of this study demonstrate that chemical castration is implemented after the convicted person has completed their primary sentence. This creates an opportunity for offenders to escape. Furthermore, prosecutors and police must coordinate again to carry out the arrest. If the results of the clinical examination indicate that the offender is eligible for chemical castration, the professional code of ethics for doctors and healthcare workers in Indonesia considers that castration would tarnish the medical profession. Here, it is evident that a court ruling with the force of law lacks enforceability. This article argues that Article 9(c) should be reformulated to require a clinical assessment and, where legally and medically permissible, the execution of chemical castration before the convict’s release. Where the convict is declared medically unfit, the judgment should not be treated as void but should trigger a judicially supervised substitution mechanism involving electronic monitoring, mandatory rehabilitation and post-release supervision.